2018
DOI: 10.1186/s12937-018-0401-7
|View full text |Cite
|
Sign up to set email alerts
|

Food-related behaviours among individuals with overweight/obesity and normal body weight

Abstract: BackgroundEmotional eating is a factor associated with a negative body image and other problematic eating behaviours. In this context little is known about differences between individuals with overweight and obesity and those with normal body weight. The main aim of the study was to evaluate the role of emotional eating in the relationship between the desire to consume chocolate and the wish to avoid social situations related to food and body exposures. For this purpose, we tested the direct, indirect and buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
(79 reference statements)
1
17
0
1
Order By: Relevance
“…In addition, our set of observations is coherent with previous studies (mentioned in the Introduction section) which describe that: (1) negative emotional functioning may influence increase emotional eating [e.g., 8,12,20–24], (2) stress leads to more frequently snacking [ 19 ], (3) emotional eating contributes to increase BMI [e.g., 20,25], and (4) snacking may be positively associated with emotional eating [ 1 ]. Some of our results are not consistent with research highlighting the importance of negative emotions [ 19 ] and dysregulation of emotions [ 22 ] for snacking and the impact of snacking on BMI [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, our set of observations is coherent with previous studies (mentioned in the Introduction section) which describe that: (1) negative emotional functioning may influence increase emotional eating [e.g., 8,12,20–24], (2) stress leads to more frequently snacking [ 19 ], (3) emotional eating contributes to increase BMI [e.g., 20,25], and (4) snacking may be positively associated with emotional eating [ 1 ]. Some of our results are not consistent with research highlighting the importance of negative emotions [ 19 ] and dysregulation of emotions [ 22 ] for snacking and the impact of snacking on BMI [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it is important to note that in the present study, we used a measure of snacking based on a single item. However, in our previous research using this single-item scale, snacking was a reliable predictor of similar eating behaviours [ 1 ]. In the future research to measure snacking, more comprehensive dietary measure could be used (e.g., Dietary History Questionnaire, the Automated Self-Administered 24-h Dietary Assessment Tool).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, we did not stratify by BMI. Previous studies have shown that overweight and obese individuals might have different eating behaviors and perceptions about healthy eating, compared to healthy weight individuals [ 44 ]. However, participants in this study had a wide BMI range, representing all body composition categories.…”
Section: Discussionmentioning
confidence: 99%